Asymmetric topological pumping in nonparaxial photonics - Qingqing Cheng; Huaiqiang Wang; Yongguan Ke; Tao Chen; Ye Yu; Yuri S. Kivshar; Chaohong Lee; Yiming Pan (Nature Communications, 2022)
The understanding of the topological properties of light is at the base of the future optical devices development. In this work the authors aim to suggesting a different paradigm for topological transport and manipulation of nonparaxial light, paving the way toward the new developments in the field of topological photonics